Congenital Talipes Equinovarus (CTEV): A Literature Review - Saputra, Kurniawan Aditya; Kamilah, Nilam Nurmilatun; Lovely, Anjela Fatma; Faqih, Fauzan; Nazilinly, Fitri; Murniati, Rinesita; Firdaus, Royan Alfian; Mutia, Baiq Marceliya Anjani; Putri, Radiah Meilani; Putra, Rifky Sandya Rakadi; Rahman, Hadian (PROMOTOR, 2025)
Congenital talipes equinovarus (CTEV) is a congenital foot deformity affecting one or both extremities with a global prevalence estimated at 0.6-1.5 per 1000 live births. The exact etiology of CTEV remains unclear, although genetic and environmental factors are thought to play significant roles. The deformities in CTEV typically include malposition of the tarsal bones, calf muscle atrophy, and shortening of the affected limb. This article aims to provide additional information on CTEV to facilitate early screening and improve patient prognosis. This study employed a literature review method covering the definition, epidemiology, etiology, pathological anatomy, pathogenesis, clinical manifestations, diagnosis, scoring systems, and management of CTEV. Data were obtained through electronic searches in PubMed, ProQuest, ScienceDirect, and Google Scholar databases.